Long term follow-up of MRD guided treatment of Ibrutinib plus Venetoclax for Relapsed CLL: phase 2 VISION/HO141 trial - Niemann, Carsten Utoft; Dubois, Julie; Nasserinejad, Kazem; da Cunha-Bang, Caspar; Kersting, Sabina; Enggaard, Lisbeth; Veldhuis, Gerrit-Jan; Mous, Rogier; Mellink, Clemens H.M.; van der Kevie-Kersemaekers, Anne-Marie F.; Dobber, Johan A.; Bjørn Poulsen, Christian; et al. (American Society of Hematology, 2025)
Patients with relapsed/refractory (RR) chronic lymphocytic leukemia (CLL) are treated with fixed-duration Bcl-2 inhibitors + CD20 monoclonal antibodies or continuous BTK inhibitors. While continuous treatment may lead to cumulative toxicity or resistance, fixed-duration treatment may lead to under-treatment and early relapse. Efficacy and safety of minimal residual disease (MRD)-guided treatment cessation of ibrutinib+venetoclax (I+V) with reinitiated I+V upon MRD conversion was evaluated in the randomized VISION/HO41 Phase II study. Four-year follow-up including long-term toxicity and MRD kinetics are reported. Patients received ibrutinib for two (28-day) cycles followed by 13 cycles of I+V. Patients reaching undetectable (u)MRD4 (<10-4, flow cytometry) in blood and bone marrow at cycle 15 (C15) were randomized 2:1 between treatment cessation with reinitiated I+V upon detectable (d)MRD2 (≥10-2) and ibrutinib maintenance. MRD4 positive patients at C15 remained on ibrutinib (dMRD4 arm). With a median of 51.7 months, the estimated 4-years overall survival (OS) was 88%, progression free survival (PFS) was 81%; 14% of patients required next-line treatment (NT). For patients randomized to treatment cessation, 40% had reinitiated therapy per protocol due to dMRD2. No difference between treatment cessation, ibrutinib maintenance or dMRD4-arm continuing ibrutinib was seen for OS, PFS or NT in Landmark analysis from C15 time of randomization. Lower toxicity was demonstrated for the treatment cessation arm. MRD-guided cessation and reinitiation of I+V for RR CLL is feasible, reduces toxicity compared to indefinite BTK inhibitor while providing comparable PFS rates. NCT03226301.